Interactions between Metopolophium festucae cerealium (Hemiptera: Aphididae) and Barley yellow dwarf virus (BYDV-PAV). Issue 1 (20th February 2016) - Sadeghi, S. E.; Bjur, J.; Ingwell, L.; Unger, L.; Bosque-Pérez, N. A.; Eigenbrode, S. D.
Abstract: Interactions between an invasive aphid, Metopolophium festucae (Theobald) subsp. cerealium, and Barley yellow dwarf virus (BYDV-PAV) were studied under laboratory conditions. M. festucae cerealium is an economic pest of wheat and barley that has recently been found in high population densities in wheat in the Pacific Northwest of the United States . BYDV-PAV is the most prevalent and injurious species of BYDV worldwide and in the Pacific Northwest. Although M. festucae sensu stricto (Theobald 1917) has been reported previously as a vector of some BYDV isolates, there is no confirmed transmission of BYDV by M. festucae cerealium. Two experiments examined the ability of M. festucae cerealium to transmit BYDV-PAV. The first used single aphids caged to indicator plants of a BYDV-susceptible winter wheat cultivar and the second used multiple aphids on each test plant. M. festucae cerealium did not transmit BYDV-PAV in either experiment, whereas transmission by a known BYDV vector, Rhopalosiphum padi L., was consistently high (≥93%). A third experiment compared the intrinsic growth rate, days until first reproduction and daily reproduction by M. festucae cerealium on sham-inoculated and BYDV-PAV-infected wheat, but detected no differences. The findings are reviewed in light published data on M. festucae species, BYDV transmission, and the potential pest status of this new invading aphid.